(untitled) (ASEAN Engineering Journal, 2023)
Drilling mud has an important role in drilling operations, as well as lifting the cutting to the surface, controlling the pressure of the formation, and preventing the collapse of the borehole. Therefore, the drilling operations can be continued without obstacles. The function of the drilling mud depends on the conditions of the formation to be drilled for optimal results. One of the main functions is to lift cutting from a bottom hole to the surface. In the annulus, the minimum speed for lifting the cutting to the surface was calculated. The Cutting Capacity Annulus (CCA) is the value of the level of solids in the annulus. The proper concentration of cutting in the annulus is not more than 5%, to avoid drilling problems, such as decreased rate of penetration (ROP), increased drag and torque, and stuck pipe related to hole cleaning problems. In analyzing the lifting ability of cutting, CCA is very suitable to be used because it accounts for the parameters of ROP value. This study conducted a comparison of two types of natural polymers that have a function to help the hole cleaning in the drilling process. The two types of polymers are cellulose polymers (drispac) and polysaccharide polymers (starch). Furthermore, it also had been tested on a field scale using the cutting transport ratio (CTR) method to find out how much ratio is obtained in the two types of polymer mud. Based on the test of the two mud samples on the cutting removal process in the CCA method at a temperature of 150oF, the mud samples containing starch ranged from 1.0731% to 1.0792%, while the mud samples containing drispac ranged from 1.0730% to 1.0793%. At 200oF the mud samples containing starch ranged from 0.7357% to 1.3604%, while the mud samples containing drispac ranged from 0.7357% to 1.3603%. At a temperature of 250oF, the mud samples containing starch ranged from 0.2652% to 0.4903%, while the mud samples containing drispac ranged from 0.265178% to 0.4907%. Although the density of the starch-containing mud sample was greater than drispac, the CCA value did not have much effect due to the difference in density of the two mud samples of 0.1 ppg. Both samples were able to optimally lift the cutting above the surface because the CCA value was less than 5%.